BENTUK PENGELOLAAN KELAS OLEH GURU DALAM PEMBELAJARAN SOSIOLOGI DI KELAS XI IPS 1 SMA NEGERI I SIBERUT UTARA KABUPATEN KEPULAUAN MENTAWAI - Ike Nurjana; Yenni Melia; Yanti Sri Wahyuni (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
The problem in this study is that when the teacher teches in the classroom, it is found that student often come in and out during teaching and learning activities and student respond to the actions of their friends who make jokes so that the class becomes noisy and the teacher has difficulty in creating comfortable atmosphere in the learning process of sociology, so that the expected class management does not run as sxpected because it stiil encounsters obstacles in its implementation. The purpose of this study was to describe the form of classroom management carried out by teacher in learning sociology in class XI IPS I student at SMA Negeri I Siberut Utara Mentawai Islands Regency.The teory in research is the Behavioristic theory proposed by Burhus Frederic Skinner. This research was conducted with a qualitative approach. In the selection of informants using purposive sampling technique with the number of informants 6 people. The types of data used in this research are primary data and secondary data. Data collection methods used are non-participant observation, in-depth interviews and document studies. Meanwhile, the data analysis unit used by the group with data analysis was Milles Huberman, namely data collection, data reduction, data presentation and drawing conclusions. The result showed that the form of classroom management by teachers in learning sociology in class XI IPS I SMA Negeri I Siberut Utara Mentawai Islands Regency it can be concluded that there are 3 ways to manage classes namely physical 1. Physical management activities include: a) the room where the teaching and learning process takes place,. b) Seating arrangement, c) Ventilation and light regulation, d) Arrangement of goods, e)Arrangement of teaching tools 2. Time management activities carried out by the teacher by entering the classroom the teacher enter according to the lesson schedule and the teacher has allocated time in opening the lesson, explaining, and closing the lesson 3. The activity of managing student by means when while studying it is found that students who like to seize in class are told to leave or not to be moved to the front seat. aiaf the student is found not to make the student own assignment, he will be expelled from class.